Influence of palmitoylation in axonal transport mechanisms in neurodegenerative diseases - B. S., Praveen; Talwar, Priti (Frontiers in Cellular Neuroscience, 2025)
Progressive functional loss and death of neurons are characteristics of neurodegenerative diseases such as Alzheimer’s disease (AD), Amyotrophic lateral sclerosis (ALS), and Parkinson’s disease (PD). These diseases are often linked with disruptions in axonal transport and synaptic functions. Accumulation of misfolded proteins is observed as a commonly shared pathology for these diseases, where aberrant accumulation of amyloid beta (Aβ), tau, α-synuclein (α-syn) and TAR DNA-binding protein 43 (TDP-43), are found in AD, PD and ALS, respectively. These accumulations are observed to be involved in disrupting axonal transport and compromising neuronal survival. Axonal transport is an essential process where proper functioning of the transport mechanism is important for maintaining neuronal hemostasis by transporting of proteins, organelles and neurotransmitter complexes. This review explores the role of palmitoylation in regulating neuronal axonal transport and their impact on other neuronal functions along with neurodegeneration mechanisms. Palmitoylation is a reversible lipid modification, which is widely studied second to phosphorylation. Enzymes like palmitoyl acyltransferases and acyl-protein thioesterases are responsible for attachment and detachment of palmitic acid causing palmitoylation and depalmitoylation of neuronal proteins. In axonal transport, palmitoylation influences the localization and functioning of the proteins, which connectively plays a role in synaptic stability by interacting with synaptic scaffolding proteins and neurotransmission receptors.